2021
DOI: 10.1186/s12884-021-03785-7
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensively addressing postpartum maternal health: a content and image review of commercially available mobile health apps

Abstract: Background The United States is currently facing a maternal morbidity and mortality crisis, with the highest rates of any resource-rich nation. In efforts to address this, new guidelines for postpartum care suggest that mobile health (mHealth) apps can help provide complementary clinical support for new mothers during the postpartum period. However, to date no study has evaluated the quality of existing mHealth tools targeted to this time period in terms of sufficiency of maternal health inform… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 54 publications
(59 reference statements)
1
16
0
Order By: Relevance
“…The widespread adoption of mobile phones and health-related Apps might highlight a significant opportunity to impact health behavior globally, particularly in low- and middle-income countries [ 35 ]; a steady increase in the rigorous evaluation of Apps aims to modify behavior to promote health and manage disease [ 36 ]. Moreover, using mHealth Apps as a widespread form of supplementary clinical support showed promise with regards to increasing patient education, narrowing the knowledge gap in health-disparate communities, and even reducing the burden on the care partner [ 37 , 38 ]. Targeted at primary care patients, the cancer prevention mobile App and mHealth program could facilitate behavioral change to reduce the risk of cancer [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The widespread adoption of mobile phones and health-related Apps might highlight a significant opportunity to impact health behavior globally, particularly in low- and middle-income countries [ 35 ]; a steady increase in the rigorous evaluation of Apps aims to modify behavior to promote health and manage disease [ 36 ]. Moreover, using mHealth Apps as a widespread form of supplementary clinical support showed promise with regards to increasing patient education, narrowing the knowledge gap in health-disparate communities, and even reducing the burden on the care partner [ 37 , 38 ]. Targeted at primary care patients, the cancer prevention mobile App and mHealth program could facilitate behavioral change to reduce the risk of cancer [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main factor determining the value of an application may be its ability to provide meaningful, accurate, and timely information to the user (43). Tucker et al assessed the effectiveness of health mobile apps for new mothers during the postpartum period and showed that the current general apps do not provide enough information about maternal health, but those providing more evidence-based information with functional design meet most of these standards, however, they are unlikely to be downloaded by users (44). Therefore, it seems that although most of the apps reviewed were not specialized for students, most studies have emphasized the need to include evidence-based information to foster the accuracy of the information contained (45).…”
Section: Discussionmentioning
confidence: 99%
“…There is important mHealth work being conducted for postpartum women, with the most robust pool of programs focusing on postpartum depression (Kocak et al, 2021 ; Saad et al, 2021 , Zhou et al, 2022 ). More needs to be done to ensure the mHealth efforts are accessible, comprehensive and evidence-based (Tucker et al, 2021 ). The Joyuus web application is designed to provide a comprehensive mHealth experience, accessible through a web browser rather than an Apple or Google App paywall, to address the self-care needs of postpartum women.…”
Section: Objectivesmentioning
confidence: 99%